The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/aln.0000000000003149
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Complement C5a Protects Mice with Pneumococcal Pulmonary Sepsis

Abstract: Background Community-acquired pneumonia and associated sepsis cause high mortality despite antibiotic treatment. Uncontrolled inflammatory host responses contribute to the unfavorable outcome by driving lung and extrapulmonary organ failure. The complement fragment C5a holds significant proinflammatory functions and is associated with tissue damage in various inflammatory conditions. The authors hypothesized that C5a concentrations are increased in pneumonia and C5a neutralization promotes ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Further, Xin et al 72 described that escin could increase glucocorticoid receptor in the lung of animals, especially reversing the decrease of glucocorticoid receptor resulting from LPS, supporting the idea that the anti‐inflammatory effect of escin could involve the upregulation of glucocorticoid receptor with an increase of endogenous antioxidant activity. In a mouse model of pneumococcal pneumonia, a 4‐day administration of escin (1.8 mg/kg intravenously), significantly reduced lung inflammation, suggesting a role for escin as add‐on treatment 73,74 …”
Section: Anti‐inflammatory Antiviral Effects Of Escin In Vitro and Imentioning
confidence: 98%
“…Further, Xin et al 72 described that escin could increase glucocorticoid receptor in the lung of animals, especially reversing the decrease of glucocorticoid receptor resulting from LPS, supporting the idea that the anti‐inflammatory effect of escin could involve the upregulation of glucocorticoid receptor with an increase of endogenous antioxidant activity. In a mouse model of pneumococcal pneumonia, a 4‐day administration of escin (1.8 mg/kg intravenously), significantly reduced lung inflammation, suggesting a role for escin as add‐on treatment 73,74 …”
Section: Anti‐inflammatory Antiviral Effects Of Escin In Vitro and Imentioning
confidence: 98%
“…Aptamers have also been developed to block C5a (Yatime et al, 2015;Hyzewicz et al, 2017) and C5aR1 (Kumar, 2018). A mouse study showed protection against pneumococcal sepsis using an aptamer blocking C5a (Müller-Redetzky et al, 2020), but the aptamers have not yet reached the clinic. 4.…”
Section: Monoclonal Antibodies and Their Derivativesmentioning
confidence: 99%
“…Concerning deployment of complement therapeutics during experimental sepsis, complement depletion [ 161 ], C1 inhibition [ 162 ], specific blockade of C5a [ 118 , 163 ], C5aR1 [ 164 ], genetic deficiency in C5 [ 165 ], or genetic absence of C6 [ 166 , 167 ] have been demonstrated to improve sepsis-induced pulmonary inflammation on a morphological and/or functional level.…”
Section: Complement Interactions In the Lungsmentioning
confidence: 99%